Time-Domain Optical Coherence Tomography System for Determining The Extinction Coefficient and Group Refractive Index of Gelatin-based Skin Phantoms - Maria Cecilia Galvez; Edgar Vallar; Tatsuo Shiina; Ernest Macalalad; Paulito Mandia (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2021)
Optical Coherence Tomography (OCT) is a non-invasive, non-destructive optical imaging technique that uses a low coherence interferometer to obtain real-time cross-sectional images of samples. OCT is notably used in biomedical applications including ophthalmology and dermatology. Aside from generating cross-sectional images, axial scans can also provide additional information about its optical properties such as extinction coefficient and refractive index. This study determines the extinction coefficients and group refractive indices of gelatin-based skin phantoms using a portable time-domain (TD) – OCT system. The gelatin-based skin phantoms were fabricated with varying concentrations of titanium dioxide (TiO2), while keeping the amount of both gelatin and water constant. By changing the proportion of the gelatin powder and TiO2, skin phantoms can then be fabricated to mimic various skin conditions, both pathologic and non-pathologic. Results of the study found a positive correlation of extinction coefficient and refractive index with TiO2 concentration. Thus, increasing TiO2 concentration also increases both extinction coefficient and group refractive index. The median extinction coefficient values of the phantoms ranged from 4.29 mm−1 to 8.48 mm−1. Literature showed that the epidermis can have extinction coefficients of 1.64-7.3 mm−1. For refractive indices of the fabricated phantoms, values ranged from 1.32 to 1.48, while studies on human participants showed that human skin has refractive index values of 1.34-1.56. Based on these properties, it is feasible to fabricate phantoms simulating the optical properties of human skin.